Hours vs employment in response to demand shocks - Robert A. Hart (IZA World of Labor, 2023)
The responses of working hours and employment levels to temporary negative demand shocks like those caused by the Great Recession in 2007-2008 and the Covid-19 pandemic in 2020-2022 have shown that consideration of both is important. Workers' desired rises in working hours in times of recession also serve to modify the standard measure of unemployment. During Covid-19, both jobs and earnings were temporarily protected among workers forced into short-time work schemes, providing a useful comparison with the provision of improved unemployment insurance to unemployed workers at that time.
Keywords: E24; E32; J23; 330; demand shocks; hours; employment; job retention